A high gain and low-offset current-mode instrumentation amplifier using differential difference current conveyors - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2016)
In this work, a current-mode high CMRR and low offset instrumentation amplifier is proposed. In the structure, only differential difference current conveyors (DDCC) are employed. The offset of the instrumentation amplifier is suppressed using an integrator feedback stage. The CMRR of the system is simulated using mismatch models for the DDCC elements employed. The CMRR of the instrumentation amplifier is independent of resistor mismatches, and, high CMRR is achieved if good matching of the differential transistors of each current conveyor is provided. The proposed instrumentation amplifier is designed using 0.35μm technology and simulated using HSPICE. The designed instrumentation amplifier provides high CMRR with low offset and it is especially suitable for AC coupled measurements. The simplicity of the design structure is the main advantage of the provided design where only DDCC elements are required for high CMRR and high output swing. © 2015 IEEE.
Keywords: CMRR; current-conveyor; current-mode circuits; DDCC; low offset instrumentation amplifier